Identification of transcriptional targets associated with the expression of p210 Bcr-Abl - HICKEY, FIONNUALA (My University, 2006)
Objectives: Chronic myeloid leukaemia is caused by the expression of the p210 Bcr-Abl fusion protein which results from the Philadelphia translocation, t(9;22). This oncogene has been the focus of extensive research. However, the molecular mechanisms responsible for the haematological malignancy are not fully understood. The main objective of the current study was to identify novel transcriptional targets of Bcr-Abl. Methods: In order to achieve this, microarrays were employed in order to conduct a genome-wide expression analysis comparing 32D cells with a transfected clone expressing high levels of p210 Bcr-Abl. Quantitative RT-PCR was employed in order to confirm the observed increase/decrease in expression for a number of the deregulated genes. Results and conclusions: This comparison identified 138 genes of known function showing altered expression in response to Bcr-Abl mediated signalling. Among the genes found to be upregulated in response to p210 Bcr-Abl were aldolase 1A and phosphofructokinase, both of which encode key enzymes in the glycolytic pathway. As a consequence of this, we demonstrate that the rate of glycolysis is significantly increased in Bcr-Abl expressing cells in a PI3K-dependent manner. Our results also indicate altered expression of genes involved in cell proliferation, cell adhesion and cell signalling.
PUBLISHED
Keywords: Bcr-Abl; chronic myeloid leukaemia; Philadelphia chromosome; microarray analysis; gene expression profiling; glycolysis; proliferation; PI3K